The application of theory of planned behaviour on business zakah compliance in Yemen: a proposed framework - Nashwan, Saeed Awadh; Abdul Jabbar, Hijattulah; Romle, Abd Rahim (IDOSI Publications, 2016)
Zakah (the alm tax), as one of the five pillars of Islam, aims at poverty reduction and eradication among Muslim community.Similar to tax, understanding the issue of non-compliance is highly relevant to the context of Zakah as well. In Yemen, the proceeds from Zakah are considered low, probably due to compliance gap.Several studies have been conducted on the issues of Zakah compliance in some Islamic countries and most of the literature focused on employment income and saving, with less attention given to business Zakah.The core objective of this paper is to propose a framework for examining factors influencing the current level of Zakah compliance by business enterprises through the theory of planned behaviour.This paper provides a framework to researchers and guidance to the Zakah authorities to better understand the Zakah payer and eventually develop a more effective business Zakah compliance programs to encourage higher intention to pay Zakah among business owners.